Anaesthetic‐induced cardioprotection in an experimental model of the Takotsubo syndrome – isoflurane vs. propofol. Issue 3 (22nd January 2017) - Oras, J.; Redfors, B.; Ali, A.; Lundgren, J.; Sihlbom, C.; Thorsell, A.; Seeman‐Lodding, H.; Omerovic, E.; Ricksten, S.‐E.
Abstract : Background: Takotsubo syndrome (TS) is an acute cardiac condition with a substantial mortality for which no specific treatment is available. We have previously shown that isoflurane attenuates the development of left ventricular (LV) dysfunction in an experimental TS‐model. We compared the effects of equi‐anaesthetic doses of isoflurane, propofol and ketamine+midazolam on haemodynamics, global and regional LV systolic function and the activation of intracellular metabolic pathways in experimental TS. We hypothesized that cardioprotection in experimental TS is specific for isoflurane. Methods: Forty‐five rats were randomized to isoflurane (0.6 MAC, n = 15), propofol (bolus 200 mg/kg+360 mg/kg/h, n = 15) or ketamine (100 mg/kg)+midazolam (10 mg/kg, n = 15) anaesthesia. Arterial pressure, heart rate and body temperature were continuously measured and arterial blood gas analysis was performed intermittently. TS was induced by intraperitoneal injection of isoprenaline, 50 mg/kg. LV echocardiography was performed 90 min after isoprenaline injection. Apical cardiac tissue was analysed by global discovery proteomics and pathway analysis. Results: Isoprenaline‐induced changes in arterial blood pressure, heart rate or body temperature did not differ between groups. LV ejection fraction was higher and extent of LV akinesia was lower with isoflurane, when compared with the propofol and the ketamine+midazolam groups. In this TS‐model, the proteomic analysis revealed an up‐regulation of pathways involved in inflammation, coagulation, endocytosis and lipid metabolism. This up‐regulation was clearly attenuated with isoflurane compared to propofol. Conclusion: In an experimental model of TS, isoflurane, but not propofol, exerts a cardioprotective effect. The proteomic analysis suggests that inflammation might be involved in pathogenesis of TS.